Smart home energy management system based on a hybrid wireless network architecture - Jebroni, Zakariae (2020)
Currently, in electrical energy sector, due to the population growth and the increasing energy consumption demand, the electrical grid is becoming more and more complex. This creates new challenges in term of electrical energy management. Our contribution in this area, presented in this paper, consists of the design, implementation and test of a wireless monitoring and control system for household electrical appliances. This system offers to the residential customers a helpful tool to monitor and control the energy consumption of their household appliances. The developed system is composed by a set of components connected to each other using wireless network technologies: the monitoring devices, the gateway and the client devices (with the respective user interface). For the development of this system, we opted to use a hybrid wireless network solution based on Wi-Fi and Bluetooth Low Energy (BLE). We describe the design and the implementation of the monitoring device hardware, as well as the calculation methodologies to obtain the electrical quantities and to reduce as much as possible the measurement errors. This paper describes also the development of the BLE/Wi-Fi gateway and the Graphical User Interface (GUI). The performance of the developed monitoring device was evaluated by means of experimental tests, where we achieved a voltage measurement error below 0.2% and a current measurement error below 0.5%.